MAKING WORK EFFECTIVENESS IN KELURAHAN DUREN JAYA BEKASI JAWA BARAT - Siswandi Siswandi; Bintang Narpati; Abdul Gofur (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
The purpose of this study is to measure the impact of archival and computer training on increasing the effectiveness of work in Duren Jaya Bekasi Urban Village. The method used in this research is using quantitative descriptive analysis involving all employees of Kelurahan Duren Jaya Bekasi using random sampling technique with proportional random sampling of 35 (thirty five) people. Data collection technique used is questionnaire method supported by documentation method. Data analysis technique used is double linear regression analysis technique. Based on the results of this study, it can be concluded that: (1) There is a significant positive influence between the Archives Training on the effectiveness of the employee's work in Duren Jaya Bekasi Sub-district (2) There is a significant positive influence between the Computer Training on the effectiveness of the employee in Kelurahan Duren Jaya Bekasi (3) There is a significant positive influence between the Archives and Computer Training on the effectiveness of the employees of Kelurahan Duren Jaya Bekasi. Skills in managing archives and computers can make the effectiveness of employment Kelurahan Duren Jaya Bekasi more increased. The results of this study indicate that archival and computer training has an influence of 82.6% towards increasing employee effectiveness. Keywords: filing, computer and work effectiveness.